Developing an integrated framework of healthcare leaders' resilience - Charlotte Förster; Stephanie Duchek; Silke Geithner; Maxie Krägler (Review of Managerial Science, 2022)
Healthcare institutions have been under pressure for years now, climaxing in the COVID-19 crisis. Even if they are not operating at a trouble spot of the current COVID-19 pandemic, healthcare leaders need to be highly resilient to remain effective as well as staying healthy themselves. The purpose of this study is to shed light on healthcare leaders' challenges and, more important, their specific resilience factors. By doing so, we can expand the knowledge of this fragmented research field and deliver an integrated framework that has so far been lacking. We conducted 20 in-depth interviews with healthcare leaders. More precisely, 35% (7) of our interviewees were physicians, 55% (11) worked in nursing, and 10% (2) were nonclinical professionals, with 50% (10) of our participants working in upper, 40% (8) in middle, and 10% (2) in lower leadership positions. Based on a qualitative content analysis approach, we identified main healthcare leaders' challenges as well as crucial resilience factors (i.e., individual, situational, and behavioral factors). By integrating insights from contemporary leadership and work-related resilience research, we were able to develop an integrated framework of healthcare leaders' resilience. Considering resilience as a context-dependent construct, we are contributing to the resilience and healthcare literature by investigating the specialty of healthcare leaders' resilience. This study is contributing to the future development of resilience interventions in healthcare organizations that might help not only healthcare leaders to better cope with critical situations but also promote resilience development among their followers and organizations.
Keywords: M12; 650; Healthcare leaders; Healthcare leaders' resilience; Healthcare leaders' challenges; Workplace resilience